PLANNING OF SECONDARY SCHOOL LOCATION AT SUBCENTRE OF MEDAN SELAYANG SERVICE BASED ON GEOGRAPHIC INFORMATON SYSTEM - Mansyur Hidayat Pasaribu (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2017)
This research aimed to solve the problem of requirement of facility and infrastructure of high school education year 2030 at 4 sub-districts in sub department of Medan Selayang. By knowing the number of junior high school student we can calculate requirement of middle school infrastructure needed. The need for secondary school building infrastructure at the Medan Selayang service sub-center in 2030 is calculated based on the number of population aged 0-4 years in 2016 as users of secondary education services in the planning year. The need for the number of new school units based on the maximum capacity of study groups available in each school in the study area, the lack of learning groups is met through new classroom addition programs and the addition of new school units. With the population of middle school age in 2030 in four districts amounting to 33,299, it is required to provide 1 unit of new school in Medan Baru sub-district, 1 unit of new school in Medan Selayang sub-district, 2 units of new school in Medan Tuntungan sub-district. The lack of study group in Medan Baru sub-district can be fulfilled by adding new classroom based on the availability of school land. Planning of school location in the addition of new school unit based on spatial analysis using geographic information system application. Method of research used is descriptive method quantitatively. Quantitative analysis done By using Geographic Information System. Analysis is done based on the factors that influence the selection of school location which consists of service coverage factors, distribution pattern factors, accessibility factors and land use factors. From the results of analysis based on spatial data found sowed that the area has not been served in the region Planning. This underserved area became a zone in the determination of secondary school location planning at the Medan Selayang service sub-center.